How to create an artist lie? - Nunes, Fabio Oliveira [UNESP] (Association for Computing Machinery (ACM), 2017)
Artist lies [21] are artistic incursions that surpass the simulacra of the art to act in the quotidian reality. They imitate to be what they are not. These incursions can be created from an appropriate context, gaming with public expectations, being much more effective when they use technological media in their achievements. In fact, these lying incursions should motivate a critical reflection on the need for more attention to deal with other lies.
Keywords: Contemporary art; Lie; Media art